Parental Perceptions of Early Childhood Education in Muara Pinang Village, Empat Lawang Regency - Adelia, Masayu; Handayani, Tutut; Fahmi, Fahmi; Murtopo, Ali (Journal of Early Childhood Education (JECE), 2024)
The education that children will get is inseparable from the perceptions of parents who send or do not send their children to school and every perception conveyed by parents is influenced by several factors. Therefore, this study aims to find out how the perceptions held by parents regarding early childhood education and find out the reasons behind the perceptions conveyed. The research method used is a type of qualitative research, while the data collection techniques used are observation, interviews, and documentation. The results show that parents have similarities and differences in conveying perceptions of early childhood education, namely: Parents who send their children to school said that Early Childhood Education is very important because they can gain basic knowledge, making it easier for children to enter primary school. Meanwhile, parents who do not send their children to school say Early Childhood Education is important and quite important, but most of these parents say education can be obtained at home without having to be enrolled in PAUD. The factors underlying parents convey these perceptions in the form of internal and external factors. Internal factors include the parents-children closeness and the reasons for sending and not sending children to school. External factors are environment, educational background, work, and school fees.